Предмет: Математика,
автор: Стейси33
Решите уравнение:
4(1-0,5х)=-2(3+2х)
Ответы
Автор ответа:
0
4(1-0,5х)=-2(3+2х)
4-2х=-6-4х
-2х+4х=-6-4
2х=-10
х=(-10):2
х=-5
4-2х=-6-4х
-2х+4х=-6-4
2х=-10
х=(-10):2
х=-5
Автор ответа:
0
4(1-0,5х)=-2(3+2х)
4-2х=-6-4х
-2х+4х=-6-4
2х=-10
х=-10:2
х=-5
4-2х=-6-4х
-2х+4х=-6-4
2х=-10
х=-10:2
х=-5
Похожие вопросы
Предмет: Биология,
автор: olesyazenit2009
Предмет: Биология,
автор: lalkavak
Предмет: Математика,
автор: cekulaevamonika
Предмет: Математика,
автор: spleshu
Предмет: Математика,
автор: Аноним